(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article focuses on the surreal imagery of P. Tychyna on the material of his early work, in particular, verses from the collection «Solar Clarinet». Attention is drawn to the presence in the works of expressively expressed emotional tonality, superrealism of allusions, illogical symbols, automatic fixation, black humor.